1992
DOI: 10.2307/2499534
|View full text |Cite
|
Sign up to set email alerts
|

Engendering Russia's History: Women in Post-Emancipation Russia and the Soviet Union

Abstract: Whether or not scholars adopted a self-consciously feminist perspective, its content places much of this initial scholarship in "contribution" history, to borrow Gerda Lerner's phrase. Such histories describe "women's contribution to, their status in and their oppression by male-defined society." 5 Partly because of the intrinsic importance of those topics, but also because they left a relatively accessible paper trail, they focus either on women of the intelligentsia or on the bolshevik attempt to liberate wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Compared with female directors in Anglo‐Saxon countries, Russian women on boards place greater emphasis on expressing moral support, empathy, and patience for their executives (Gvozdeva & Gerchikov, 2000; Yarushkin & Satonina, 2009), deeply rooted attributes in Russia's patriarchal history (Engel, 1992; Sechiyama, 2014) that remain imbedded in core social norms and guide Russian female directors in the board decision‐making process (Buck, 2012; Feifer, 2010; McCarthy & Puffer, 2008).…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with female directors in Anglo‐Saxon countries, Russian women on boards place greater emphasis on expressing moral support, empathy, and patience for their executives (Gvozdeva & Gerchikov, 2000; Yarushkin & Satonina, 2009), deeply rooted attributes in Russia's patriarchal history (Engel, 1992; Sechiyama, 2014) that remain imbedded in core social norms and guide Russian female directors in the board decision‐making process (Buck, 2012; Feifer, 2010; McCarthy & Puffer, 2008).…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Russia's geography, which occupies a significant portion of both Europe and Asia, contributes to the formation of a unique type of patriarchy at the core of Russian culture (Ryabov, 2000; Sergeeva, 2006; Shubart, 1938). Russian patriarchy maintains that family values are shaped by women, an attitude that remained unchanged during the era of the Soviet Union and feminist movements in Western countries (Buck, 2012; Engel, 1992; Pushkareva & Zolotukhina, 2017; Ryabov, 2000). Describing the main features of a Russian woman, Ryabov (2000, p. 2) states that, to them, “the beauty of a Russian woman is not in her looks but is rather in her ability to express empathy.” Indeed, according to the World Value Survey (Wave 6, 2010–2014), compared with Russian males, Russian females generally place greater value on showing “tolerance and respect for other people.” They also believe that support and respect for authority is an important societal norm.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several scholars have shown that women tend to be very active in the civic sector (Henderson 2003;Hemment 2007;Salmenniemi 2005;Sperling 1999). Women were also actively involved in both the socialist revolution and the feminist movement from the 1860s onwards (Stites 1978;Engel 1992).…”
Section: Gendered Activist Identitymentioning
confidence: 99%
“…By the nineteenth century, women of all classes were brought up within the resulting cultural matrix, dominated by polarities of veneration and contempt, adoration and anxiety. What is remarkable, in fact, is just how stable those polarities remained despite the changing social struc tures and growing intellectual ferment that characterized the century (Engel 1983, Heldt 1987.…”
Section: Myelographies and Misogyniesmentioning
confidence: 99%